Arrêt sur image et premier plan absolu dans les poèmes homériques de Michael Longley - Melanie White (Revue LISA, 2014)
This article aims at analysing the ways in which Michael Longley, in his poems inspired from the Odyssey, freeze frames the Homeric narrative and replaces it with a present out of time, extracted from the epic sweep. By frequently choosing scenes of recognition, as in the poems “Anticleia”, “Eurycleia” and “Laertes”, Longley encapsulates the reader’s attention within a lyric moment that is taken out of one of the key stages of the epic plot. Severed from all chronological and narrative perspective, this episode becomes an independent fragment. He explains his creative process thus: “From the outset, in my Homeric poems I pushed against the narrative momentum and ‘freeze-framed’ passages to release their lyric potential.” This freeze-framing creates a magnifying effect, which places each action accomplished by the epic protagonist on an absolute foreground without any wider perspective, as if each of these actions took place before the reader’s eyes, in a form of immediacy which reinforces the characteristics of the Homeric present as defined by Erich Auerbach in Mimesis. Similarly, the syntactical unity of these poems, which are often composed of one single sentence, reinforces this sense of present tense. Using diverse processes between translation and creation, Michael Longley proposes a variation on epic simultaneity by superposing different planes of reality, most remarkably thanks to the use of clauses linked by “as”, which end up being blurred into a single perspective. In this freeze-framed viewpoint, an emerging poetic consciousness is being shaped.